Structure, stability, and nature of bonding in carbon monoxide bound EX3+ complexes (E = group 14 element; X = H, F, Cl, Br, I). Issue 24 (18th July 2016) - Ghara, Manas; Pan, Sudip; Kumar, Anand; Merino, Gabriel; Chattaraj, Pratim K.
Abstract : A density functional theory study is performed to predict the structures and stability of carbon monoxide (CO) bound EX 3 + (E = C, Si, Ge, Sn, Pb; X = H, F, Cl, Br, I) complexes. The possibility of bonding through both C‐ and O‐sides of CO is considered. Thermochemical analysis reveals that all the dissociation processes producing CO and EX 3 + are endothermic in nature whereas most of the dissociation reactions are endergonic in nature at room temperature. The nature of bonding in EC/O bonds is analyzed via Wiberg bond index, natural population analysis, electron density, and energy decomposition analyses in conjunction with natural orbitals for chemical valence scheme. In comparison to CO stretching frequency ( ν ∼ C O ) in free CO, while a red shift is noted in O‐side binding, the C‐side binding results in a blue shift in ν ∼ C O . The relative change in ν ∼ C O values in CO bound EX 3 + complexes on changing either E or X is scrutinized and possible explanation is provided in terms of polarization in the σ‐ and π‐orbitals and the relative strength of C→E or O→E σ‐donation and E→C or E→O π‐back‐donation. © 2016 Wiley Periodicals, Inc. Abstract : The structures and stability of carbon monoxide (CO) bound EX 3 + (E = C, Si, Ge, Sn, Pb; X = H, F, Cl, Br, I) complexes are analyzed. In comparison to free CO, a red shift in CO stretching frequency is observed in O‐side binding whereas a blue shift occurs in C‐side binding. The observed change can be explained by the change in polarization in the σ‐ and π‐orbitals and the relative strength of C→E or O→E σ‐donation and E→C or E→O π‐back‐donation.